Внутрішньородове дендрорізноманіття AESCULUS L. урбосередовища Києва (адаптація до ентомостресу, вторинний метаболізм, стійкість) - Пентелюк, Олена Сергіївна (НУБіП України, 2018)
Дисертація на здобуття наукового ступеня кандидата біологічних наук зі спеціальності 06.03.01 «Лісові культури та фітомеліорація». Національний університет біоресурсів і природокористування України. Київ, 2018. У дисертаційній роботі уперше подано теоретичне, науково-методичне й експериментальне обґрунтування і нове розв’язання актуального наукового завдання щодо формування адаптивних реакцій видів роду Aesculus L. на ушкодження C. ohridella урбосередовища Києва. Установлено закономірності нагромадження вмісту і склад вторинних метаболітів, зокрема фенольних сполук у листках стійких видів та форм (культиварів) рослин роду Aesculus L. в умовах водного дефіциту. Визначено взаємозалежність між ступенем обводнення й інтенсивністю біосинтетичних процесів за відношенням РНК до ДНК у функціонально активних листках видів роду Aesculus L. на організменому рівні. У форми рослин A. hippocastanum L., яка нестійка проти C. ohridella, встановлено активізацію процесів вторинного метаболізму і нагромадження вмісту фенольних сполук, що залучаються у системи захисту клітинних структур від пошкодження гусеницями. Кількість катехінів і конденсованих танінів у листках форми рослин A. hippocastanum L., яка стійка проти C. ohridella, у 12−15 разів менша, ніж нестійкої. Динаміку вмісту флавоноїдів, як фізіологічну реакцію рослин на механічні пошкодження, описано функцією логнормальної залежності. На підставі математичної моделі вперше визначено чотири періоди нагромадження поліфенолів у листках рослин A. hippocastanum L., зокрема пролонгації, активного синтезу, насичення і біохімічної трансформації. У покривних тканинах і вторинній корі пагонів рослин роду Aesculus L. визначено накопичення вторинних метаболітів, які за кількісним й якісним складом дозволяють виділити види та гібриди в окремі групи. За видовим складом вони співпадають з секціями, які сформовані за результатами морфологічного і молекулярно-генетичного аналізів. Уперше запропоновано біохімічні маркери середньо- і високомолекулярних сполук з Rf від 0,1 до 0,3 для відбору сіянців форм A. hippocastanum L. із ознаками високої потенційної фізіологічної стійкості проти C. ohridella. Для мікроклонального розмноження стійкої проти C. ohridella і придатної для адаптації в умовах in vivo форми A. hippocastanum L. розроблено технологію поетапного морфогенезу через послідовну ініціацію калюсогенезу – дедиференціацію та диференціацію тканин з отриманням морфогенних структур
The thesis for awarding the candidate degree in biological sciences by specialty 06.03.01 «Forest Plantation and Phytomelioration». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2018. The thesis presents the results of comprehensive studies of the on ecosystem, structural – functional and molecular – biological approaches for the first time on the theoretical, scientific methodical and experimental justification. The new solution proposed for the actual scientific problem concerning to the formation of adaptive reactions for the species of the genus Aesculus L. damage to C. ohridella of the Kyiv’s urban environment. The accumulation regularity established in content and composition of secondary metabolites, especially phenolic compounds in leaves of resistant species and cultivars of genuses’ plants Aesculus L. in conditions of water insufficiency. The scientific and methodological recommendations were developed and the experimental material on optimization of biotechnological stages of clinical microproliferation in vitro resistant to C. ohridella cultivar A. hippocastanum L. for planting in Kyiv for the first time. The ecobiocultures with unique ecological properties are took into the account as promising donors for obtaining somatic clones of stable tree forms during the process of visual exploration of the green plantations of Kyiv. There were determined the interdependence between the degree of flooding and the intensity of biosynthetic processes by the ratio of RNA to DNA in functional active leaves of species of the genus Aesculus L. at the organism level. If the biochemical index of the ratio of RNA to DNA in the leaves (the binding phase of the fruits) were consisted 1.10–1.40, so the species of the genus Aesculus L. characterized by low intensity of biosynthetic processes and resistance to C. ohridella, 4.29–4.56 – average and 8.89–10.0 – high. The ratio of RNA to DNA can be use as one of the relative diagnostic signs of biological resistance for the species of the genus Aesculus L. against C. ohridella. The leaves of plants A. hippocastanum L. are unstable against the C. ohridella. The loss of physiological functions has observed, and simultaneously the secondary metabolism processes activation has accompanied by the accumulation of phenolic compounds content involved into the protection system of cell structures from the caterpillars damage. The formed leaves of plants A. hippocastanum L. characterized by the uniform distribution of phenolic compounds before the start of damage to C. ohridella. The phenolic compounds accumulation in tissues has a clearly expression vertical zonality – the largest number of which is contained in the leaves of upper plants horizons. One of the defining histochemical signs of C. ohridella resistant to A. hippocastanum L. cultivar is the substantial accumulation of specific basophilic compounds in the upper epidermis cells. They are complicated the caterpillars feeding after regeneration. The received results have doubted the decisive role for condensed tanins in forming system of physiological resistance A. hippocastanum L. against C. ohridella. The concentration of flavonoids in leaves is 3.5–4.0 times higher in the resistant cultivar in the form A. hippocastanum L., to C. ohridella, in comparison with non- resistant cultivars. It was determined, that the general flavonoids content was increased as a result of leaves integrity damage. Especially, the leaves of C. ohridella resistant to A. hippocastanum L., on the prolongation phase is longer and the saturation peak is higher. The dynamics of flavonoids content, as plants’ physiological reaction to mechanical damages, described by the function of lognormal dependence. It is based upon the mathematical model on four periods of polyphenols accumulation on the leaves of A. hippocastanum L. plants – prolongation for active synthesis, saturation and biochemical transformation are determined. The species and hybrids are identified in separate groups in the covering tissues and the bark of annual shoots of plants of the genus Aesculus L. in qualitative and quantitative composition. They almost completely coincide with the sections formed according to the results of morphological and molecular genetic analysis by species composition. High biological activity was disc0overed and the value of secondary metabolites in the processes of adaptation of aboriginal species and introducts to urbogenic factors of the medium. They were substantiated scientifically. The contribution of flavonoids evaluated for the protection system formation of A. hippocastanum L. cell structures from damage to C. ohridella. The biochemical markers were proposed for the average medium and high molecular weight compounds Rf from 0.1 to 0.3. They were received by chromatographic profiling for selection of seedlings of cultivar A. hippocastanum L. with signs of high potential physiological resistance against C. ohridella. It is advisable to use artificially awakened lateral and flower buds and shoots were took in the winter for the receiving aseptic viable actinus A. hippocastanum L. The explants use of leafy and flower meristems A. hippocastanum L. are chose in April – May from Kyiv’s isolated plantations. It is not effective way because they infected by epiphytic microflora. The microclone propagation of resistant C. ohridella to A. hippocastanum L. cultivar suitable for adaptation under conditions in vivo, methodological approaches and technology of phased indirect morphogenesis have been developed through the successive initiation of callus formation – dedifferentiation and differentiation of tissues with morphogenic structures
Keywords: види і форма (культивар) роду Aesculus L.; каштанова мінуюча міль; вторинний метаболізм; фенольні сполуки; флавоноїди; таніни; хлорофіл; мікроклональне розмноження; адаптація; стійкість; species and cultivar of the genus Aesculus L.; horse chestnut miner moth; secondary metabolism; phenolic compounds; flavonoids; tannins; chlorophyll